Humanist Expressive Speech Acts in Learning Interaction Discourse at SMK Negeri 4 Semarang - Wijayanti, Wiwik; Zulaeha, Ida; Pristiwati, Rahayu (Universitas Negeri Semarang, 2022)
Speech acts in learning interactions in the classroom are an interesting phenomenon to study because social interactions occur naturally. This study aimed to analyze the form and function of humanist expressive speech in the discourse of learning interactions at SMK Negeri 4 Semarang. This research uses a pragmatic approach. The data of this study are fragments of humanist expressive speech in learning interactions at SMK Negeri 4 Semarang. Data collection was carried out by observing the tapping technique using a recording device. Data analysis using the equivalent method. The data analysis technique is the Determining Element Sorting (PUP) technique; the validity of the data uses data triangulation and theoretical triangulation. The results of this study revealed that there are direct and indirect forms of speech. Direct speech mode includes declarative mode, imperative mode, and interrogative mode. The direct speech mode includes imperative-declarative mode and interrogative-imperative mode. The speech functions found 8 functions, including (1) thanking, (2) praising, (3) apologizing, (4) suggesting, (5) educating, (6) disappointed, (7) motivating, and (8) grateful.